Implementation of the Blended Cycle Learning Model to Increase Elementary School Students' Interest in Learning - Ratnasari, Dine Trio; Ruiyat, Suci Aprilyati (JTP - Jurnal Teknologi Pendidikan, 2025)
this study aims to analyze the effectiveness of the Blended Cycle Learning model in increasing learning interest among elementary school students in Lebak Regency. This model is designed as a systematic approach that integrates online learning, offline learning, and reflection and feedback within a continuous learning cycle. All three aim to create an adaptive learning environment that is responsive to student needs and supports active learning. The research method used was a quasi-experimental design with a pretest-posttest control group design, which allowed for direct comparison between the experimental and control groups. The sample consisted of 60 fifth-grade students from two elementary schools in Lebak Regency, who were randomly divided into two groups. The research instruments included a learning interest questionnaire for quantitative measurement, a student activity observation sheet, and a teacher interview guide for qualitative exploration. The analysis results showed a significant increase in students' learning interest scores in the experimental group compared to the control group, both in terms of average questionnaire scores and student engagement during the learning process. Teacher interviews also revealed changes in student behavior reflecting increased curiosity, learning independence, and enthusiasm for learning tasks. These findings indicate that the Blended Cycle Learning model is not only quantitatively effective in increasing learning interest but also encourages more positive changes in learning behavior. This model has proven relevant for application at the elementary level, particularly in the context of 21st-century learning, which demands technology-based pedagogical innovation and active student participation.